Strategic Policy for Strengthening Weather Services Governance through Public–Private Engagement in Indonesia - Asri Susilawati (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The rapid digital transformation of meteorological science and the emergence of private weather service providers have significantly reshaped the governance landscape of national weather services. In Indonesia, the absence of standard operating procedures and formal commercial data licensing leaves public-private interactions largely unregulated. This governance gap poses risks to information standardization, creates asymmetric economic value capture, and threatens national atmospheric data sovereignty. Utilizing the USG (Urgency, Seriousness, Growth) matrix to prioritize the core problem and a Fishbone diagram for root-cause analysis, this policy paper examines the regulatory gaps through the theoretical frameworks of collaborative governance and Public-Private Engagement (PPE). The study conducts a comparative evaluation of three regulatory alternatives: a revision of Government Regulation No. 46/2012 to strengthen State Leadership, the enactment of a Presidential Regulation for Strategic Market Expansion, and the enactment of a Presidential Regulation for a Structured PPE model. The evaluation reveals that the Presidential Regulation concerning the Governance of PPE in Value-Added Digital Weather Services is the most optimal solution. Implementing this policy will legally distinguish core public safety services from commercial sectoral services, introduce a transparent licensing framework, and mandate sustainable financial reinvestment mechanisms to ensure the continuous modernization and long-term resilience of Indonesia's national meteorological infrastructure.